ANALISIS PERUBAHAN GARIS PANTAI UJUNG BLANG KECAMATAN BANDA SAKTI KOTA LHOKSEUMAWE PADA TAHUN 2016-2020 - Safinatun Najah (Jurnal Samudra Geografi, 2022)
The coastline is the meeting line between land and sea, whose position is not fixed, changing from time to time. The purpose of this study was to determine changes in the coastline of Ujung Banda Sakti District, Lhokseumawe City, in 2016 - 2020. The research method was used by utilizing Geographic Information System (GIS) technology and remote sensing. found in the google earth pro application. The images used include 3 multitemporal images in 2016, 2018, and 2020 with the same research location. To see changes in the coastline, it can be done by overlaying images in 2016, 2018, and 2020. Image analysis is carried out using the ArcGIS 10.4.1 application., based on the results of data processing that the Ujung Blang coastline has changed in 2016-2020 along 24 meters with a reduction of 5 meters and additions of 19 meters.